As I lay dying - Faulkner, William, 1897-1962.; Vintage (London : Vintage, 2004)
Describes a family's struggle to get their mother properly buried, while they encounter catastrophes of flood and fire, as well as the chaos of their own feelings.
English.
Keywords: Fiction, English; Domestic fiction